Perilaku konsumtif sebagai mediator pengaruh affiliate TikTok dan kepercayaan terhadap minat beli Gen Z Denpasar - Ida Ayu Oka Martini; Ayu Mas Yindu Kirana (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to determine the influence of TikTok affiliate marketing and consumer trust on consumptive behavior and purchase intention, as well as the mediating role of consumptive behavior in the relationship between TikTok affiliate marketing and consumer trust on purchase intention. The research was conducted in Denpasar City, Bali, with a sample of 112 respondents. Data were analyzed using SmartPLS 4. The results show that TikTok affiliate marketing has a positive and significant effect on purchase intention, TikTok affiliate marketing has a positive and significant effect on consumptive behavior, consumer trust has a positive and significant effect on purchase intention, consumer trust has a positive and significant effect on consumptive behavior, and consumptive behavior has a positive and significant effect on purchase intention. Furthermore, consumptive behavior plays a positive and significant mediating role in the relationship between TikTok affiliate marketing and purchase intention, as well as in the relationship between consumer trust and purchase intention. Based on these findings, the researcher recommends that TikTok’s management develop a system capable of filtering reviews and recommendations from TikTok affiliates, continuously monitor product review content posted by affiliates/sellers on TikTok Affiliate, collaborate with more sellers, and oversee products offered by sellers to ensure they fulfill their promises regarding product quality and specifications.